2006
DOI: 10.1179/174328406x84058
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy study of copper–carbon nanocomposite

Abstract: A Cu210C nanocomposite has been synthesised by high energy milling of elemental powders, followed by annealing at 873 K. Phase identification and microstructure characterisation have been carried out with transmission electron microscopy. Copper grain size ranged from 10 to 120 nm for the as milled material and from 10 to 150 nm after annealing. No graphite reflections could be detected by electron diffraction in either the as milled or annealed samples. Nevertheless, both conditions contain clusters of carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The pioneering studies of Saji et al 11 and Yamane et al 12 on mechanical milling of copper-graphite mixtures with different weight ratio of graphite indicated the solubility of carbon in copper can be as high as 28.5at%, while the study carried out by Marque et al 13 on mechanical milled Cu-10at%C composite showed that the carbon content was overestimated by the former researchers and the existence of carbon nanoparticles was shown. Transmission electron microscopy examination confirmed that the microstructure of the mechanically milled Cu-10at%C nanocomposite consisted of nanostructured copper matrix dispersed with carbon nanoparticles 14 . While these studies mainly focus on the carbon solubility in copper achieved by HEMM, the microstructural evolution of copper-graphite nanocomposite powders need to be clarified with more details.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The pioneering studies of Saji et al 11 and Yamane et al 12 on mechanical milling of copper-graphite mixtures with different weight ratio of graphite indicated the solubility of carbon in copper can be as high as 28.5at%, while the study carried out by Marque et al 13 on mechanical milled Cu-10at%C composite showed that the carbon content was overestimated by the former researchers and the existence of carbon nanoparticles was shown. Transmission electron microscopy examination confirmed that the microstructure of the mechanically milled Cu-10at%C nanocomposite consisted of nanostructured copper matrix dispersed with carbon nanoparticles 14 . While these studies mainly focus on the carbon solubility in copper achieved by HEMM, the microstructural evolution of copper-graphite nanocomposite powders need to be clarified with more details.…”
Section: Introductionmentioning
confidence: 79%
“…As shown in Figure 5a, after 6 h of milling, the grain sizes of the Cu matrix were in the range of 20~40 nm, in agreement with the average crystallite size of 30 nm determined based on the XRD pattern of the powder, thus the grain size of copper determined from Williamson-Hall method was considered to be accurate. The light contrast regions marked with arrows were determined to be amorphous carbon 14 . As shown in Figure 5b, the microstructure of the 24 h milled powder particles was quite similar to that of the 6 h milled powder particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon either in the form of synthetic graphite [8] or nanodiamond [9] has proven to be very effective control process agent for MA of copper. The embrittlement mechanism involves the dispersion of nano-size carbon particles [9] in the copper matrix [10]. The present approach, using copper nitride, allows that fragmentation of copper powders during the initial stages of milling.…”
Section: Discussionmentioning
confidence: 99%
“…A microstructure refined to the nanometer scale enhances mechanical properties [5]. However, ultra-fine grain copper presents low thermal stability even at moderate temperatures [6], requiring the presence of fine particle dispersions with limited solubility to delay coarsening by a grain boundary pinning effect. Nanoscale dispersions of diamond in nanostructured copper can be used for this purpose, offering great potential in terms of strength and thermal stability.…”
Section: Introductionmentioning
confidence: 99%